2007
DOI: 10.1007/s11136-007-9287-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prevalent and incident vertebral fractures on utility: results from a patient-based and a population-based sample

Abstract: Data are scarce on the impact of vertebral fractures (VFX) on utility. The objective of this study was to assess the impact of prevalent and incident VFX on utility in both a patient-based and population-based sample. Data from the Multiple Outcomes of Raloxifene Evaluation (MORE) study (n = 550 for prevalent VFX and n = 174 for incident VFX) and the European Prospective Osteoporosis Study (EPOS) (n = 236) were used. Utility was assessed by the index score of the EQ-5D. In the MORE study, highly statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
(40 reference statements)
0
5
1
Order By: Relevance
“…In regard to HSV, in their prospective study, Strom et al reported lower mean EQ-5D-UK HSV for vertebral fracture and similar mean HSV for hip and wrist fracture groups at 1 year [54]. EQ-5D-UK HSV published from the European MORE and EPOS studies were slightly lower than those in our study [55, 56]. Hagino et al reported similar mean EQ-5D HSV at 1-year post fracture to our mean EQ-5D HSV by fracture type using Japanese preference weights [57].…”
Section: Discussioncontrasting
confidence: 55%
“…In regard to HSV, in their prospective study, Strom et al reported lower mean EQ-5D-UK HSV for vertebral fracture and similar mean HSV for hip and wrist fracture groups at 1 year [54]. EQ-5D-UK HSV published from the European MORE and EPOS studies were slightly lower than those in our study [55, 56]. Hagino et al reported similar mean EQ-5D HSV at 1-year post fracture to our mean EQ-5D HSV by fracture type using Japanese preference weights [57].…”
Section: Discussioncontrasting
confidence: 55%
“…As reported earlier, part of this finding can be explained by the fact that prevalent vertebral compression fractures worsen back pain [15,17,33,40,41,43,44] and QoL [23,35,46,47,51]. The number and severity of the prevalent fracture were especially related to the outcomes [15,35,43,47,51]. The most likely explanation for the worsening negative effect of a previous fracture is that the patients in this study who had a previous fracture(s) already were more disabled and had a lower QoL at the time when the subsequent acute fracture occurred.…”
Section: Discussionmentioning
confidence: 54%
“…Of the ICUROS results, the Swedish values were thought to be the most appropriate because they were based on the largest sample of the various country-specific cohorts and they were expected to provide a good estimator of UK HRQoL values, as northern European countries have been shown to have similar values. 231 Values from eight papers 207,[224][225][226][227][228][229][230] reporting outcomes from five distinct studies were therefore compared.…”
Section: Assessment Of Cost-effectivenessmentioning
confidence: 99%